Data mining of sustainable development process with using nightlight indicators - Putrenko, Viktor; Pashynska, Nataliia (Technology audit and production reserves, 2019)
The object of research is the process of sustainable development of territorial units on the example of the regions of Ukraine. The concept of sustainable development has become a leading development strategy for most countries in the world. One of the biggest challenges is the availability of complete and verified data for sustainable development assessment models. The method used to calculate the index of sustainable development, developed in the World Data Center for Geoinformatics and Sustainable Development of the National Technical University of Ukraine «Igor Sikorsky Kyiv Polytechnic Institute». This methodology is based on calculating the metric of the index of sustainable development based on measurements of the quality of life of the population and the components of the safety of living for individual countries and regions. For the application of the methodology at the regional level, it was suggested to use information on the night lighting of the territory received by means of remote sensing of the Earth from satellites. The character and cohesiveness of the connection between the brightness of night lighting and indicators of sustainable development are studied. It is established that the most significant link exists between indicators of the economic development index, the index of influence on climate change and night lighting of the regions of Ukraine. Based on geographic information analysis of ArcGIS software, ESRI has applied statistical zoning tools that provide opportunities for statistical processing of satellite images within the regionally or regionally allocated areas. On the basis of the mathematical apparatus of the intellectual data analysis, a global and local regression analysis of the relationships between the revealed indicators was carried out. Consideration of the cramped nature of this connection in the territorial section revealed areas with varying degrees of close ties, which is explained by the peculiarities of the socio-economic development of the territories. Due to this, it is possible to obtain the calculation of similar indicators at more detailed territorial levels, corresponding to separate regions or cities of regional significance.